2019
DOI: 10.1038/s41598-019-55172-0
|View full text |Cite
|
Sign up to set email alerts
|

A change in the zinc ion concentration reflects the maturation of insulin-producing cells generated from adipose-derived mesenchymal stem cells

Abstract: The generation of insulin-producing cells (IPCs) from pluripotent stem cells could be a breakthrough treatment for type 1 diabetes. However, development of new techniques is needed to exclude immature cells for clinical application. Dithizone staining is used to evaluate IPCs by detecting zinc. We hypothesised that zinc ion (Zn2+) dynamics reflect the IPC maturation status. Human adipose-derived stem cells were differentiated into IPCs by our two-step protocol using two-dimensional (2D) or 3D culture. The stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…1 d). The staining intensity of these NOD-IPCs was very similar to the reported intensity of isolated fresh human islets (the intensity; 244) 8 . The mRNA expression of Insulin and MafA in the generated NOD-IPCs on day 28 was significantly higher than that in ADSCs (both P < 0.05, Mann–Whitney U test, Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…1 d). The staining intensity of these NOD-IPCs was very similar to the reported intensity of isolated fresh human islets (the intensity; 244) 8 . The mRNA expression of Insulin and MafA in the generated NOD-IPCs on day 28 was significantly higher than that in ADSCs (both P < 0.05, Mann–Whitney U test, Fig.…”
Section: Resultssupporting
confidence: 76%
“…The SIs of the generated NOD-IPCs were comparable to those of previously reported human IPCs 5 10 . We previously reported that electron microscopy revealed that the nuclei of the IPCs contained dense cystic microstructures and organelles such as rough endoplasmic reticulum and mitochondria, and these dense cystic microstructures in the generated IPCs morphologically resembled insulin secretion granules observed in normal islets from naïve rat pancreas as a characteristic analysis 6 , 8 . Moreover, we described various positive markers, such as dithizone, C-peptide, insulin and PDX-1 morphological markers, and INS , MAFA , SLC39A4 , and SLC30A8 mRNA expression.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This will be important when considering the transplantation of cryopreserved IPCs. We previously reported that IPCs with poor cell quality did not secrete sufficient amounts of insulin 5 , 32 and that the transplantation of such IPCs into streptozotocin-induced immunodeficient mice did not improve blood glucose levels 8 . We have already investigated the mechanism of this phenomenon in detail (in press).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells (ADSCs) have been focused on because of their multipotency and ease of harvest. We have investigated ADSC multipotency and reported scientific evidence of insulin producing cells (IPCs) for clinical applications (7)(8)(9)(10)(11). Thus, we hypothesized that ADSCs can also self-renew and differentiate into ectodermal lineage cells, including Schwann-like cells (SLCs).…”
Section: Introductionmentioning
confidence: 99%